Evidence for autophagy-dependent pathways of rRNA turnover in Arabidopsis - Floyd, Brice E (Autophagy, 2016)
Ribosomes account for a majority of the cell's RNA and much of its protein and represent a significant investment of cellular resources. The turnover and degradation of ribosomes has been proposed to play a role in homeostasis and during stress conditions. Mechanisms for the turnover of rRNA and ribosomal proteins have not been fully elucidated. We show here that the RNS2 ribonuclease and autophagy participate in RNA turnover in Arabidopsis thaliana under normal growth conditions. An increase in autophagosome formation was seen in an rns2–2 mutant, and this increase was dependent on the core autophagy genes ATG9 and ATG5. Autophagosomes and autophagic bodies in rns2–2 mutants contain RNA and ribosomes, suggesting that autophagy is activated as an attempt to compensate for loss of rRNA degradation. Total RNA accumulates in rns2–2, atg9–4, atg5–1, rns2–2 atg9–4, and rns2–2 atg5–1 mutants, suggesting a parallel role for autophagy and RNS2 in RNA turnover. rRNA accumulates in the vacuole in rns2–2 mutants. Vacuolar accumulation of rRNA was blocked by disrupting autophagy via an rns2–2 atg5–1 double mutant but not by an rns2–2 atg9–4 double mutant, indicating that ATG5 and ATG9 function differently in this process. Our results suggest that autophagy and RNS2 are both involved in homeostatic degradation of rRNA in the vacuole.